Comparison of perceptual eye positions among patients with different degrees of anisometropia. Issue 39 (September 2017) - Yang, Cheng; Li, Xue; Zhang, Guanrong; Lan, Jianqing; Zhang, Yan; Chu, Hang; Li, Juan; Xie, Wenjuan; Wang, Shujun; Yan, Li; Zeng, Jin
Abstract : Abstract: The aim of this study is to compare the perceptual eye positions (PEPs) among patients with different degrees of anisometropia. A total of 157 patients were recruited into this retrospective study. A detailed ophthalmic examination was conducted on each patient. The degree of refractive errors in the presence of astigmatism was converted into the degree of spherical equivalent (SE). Patients were divided into 3 groups according to the interocular SE difference: severe anisometropia group with interocular SE difference ≥2.50D, mild anisometropia group with interocular SE difference ≥1.00D and <2.50D, and non-anisometropia group with interocular SE difference <1.00D. The vertical and horizontal PEP were measured by a computer-controlled perceptual examination evaluation system. The results obtained from the 3 groups were compared and analyzed. A total of 157 patients were enrolled including 32 patients in the severe anisometropia group, 37 patients in the mild anisometropia group, and 88 patients in the non-anisometropia group. The quartiles of vertical PEP pixels were as follows: 7.50 (5.00, 16.75) in the severe anisometropia group, 5.00 (2.00, 7.50) in the mild anisometropia group, and 5.00 (3.00, 9.00) in the non-anisometropia group, respectively. The vertical PEP pixel was much higher in the severe anisometropia group than that in the other two groups ( P  < .05). The quartiles of horizontal PEP pixels were as follows: 27.50 (10.75, 67.50) in the severe anisometropia group, 17.00 (7.00, 54.50) in the mild anisometropia group, and 21.50 (11.00, 60.75) in the non-anisometropia group. There were no statistically significant differences among the 3 groups ( P  > .05). There was an obvious deviation of vertical PEP in patients with anisometropia ≥2.50D, indicating that the instability of vertical PEP might be associated with the development of severe anisometropia.